Empowering Children in the Local Village with Al-Quran Literacy and Character Education - Wahyudi, Asis; Febrianti, Aristhalia Hevi (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
Because of the urgency to develop human resources in the community, this community service attempts to empower the Muslim children in Kesamben village in the district of Malang with Al-Quran literacy and character education. Using Asset Based Community Development (ABCD) procedure, this community service involved thirty-five children aged between seven and twelve years. These children participated in two programs: an Al-Quran literacy course and a character education program. The course was conducted four times a month, and so was the character education program. The result showed that the children expressed their interest in the course. Regarding the character education program, children were motivated and interactive while watching and reviewing the movie. This project has an implication for parents and community members to provide their children with the appropriate entertainment while educating them and providing an interesting and engaging Al-Quran teaching method for successful learning.